A Novel Approach to Synthesize Helix Wave Hollow Fiber Membranes for Separation Applications - Park, Sung Ryul; Kim, Jeonghoon; Ali, Aamer; Macedonio, Francesca; Drioli, Enrico (Journal of Membrane and Separation Technology, 2015)
Helix wave hollow fiber membranes are promising candidate to mitigate fouling and polarization effects in membrane operations. Current study describes a novel but simple approach to synthesize hollow fiber membranes with helix wave configuration. Poly(ether sulfone) (PES) based helix-waved hollow fiber membranes have been fabricated by dry-wet phase inversion process by using asymmetric coagulation conditions. Frequencies of the wave cycle have been observed approximately 20 and the wave length 7.1-7.6mm under the specifically required operating conditions defined by dope solution extrudate rate of 1g/min through 4cm of air-gap heights with 8.6m/min of winding speeds. On the other hand, simple hollow fibers are formed when the elongation force exerted by the winder is much higher than the surface tension of the external coagulant. The process can be useful for making polymer fibers for other applications as well.